2012
DOI: 10.1038/eye.2012.199
|View full text |Cite
|
Sign up to set email alerts
|

Post-intravitreal anti-VEGF endophthalmitis in the United Kingdom: incidence, features, risk factors, and outcomes

Abstract: Purpose To describe the incidence, features, management, and risk factors of postintravitreal anti-VEGF endophthalmitis (PIAE) in patients undergoing treatment for exudative age-related macular degeneration in the United Kingdom. Methods Prospective observational case control study. Forty-seven cases of PIAE were identified through the British Ophthalmological

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
98
2
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 124 publications
(110 citation statements)
references
References 46 publications
(81 reference statements)
5
98
2
5
Order By: Relevance
“…2 The largest UK prospective study identified 47 cases through the British Ophthalmological Surveillance Unit over a 15-month period, but the denominator figure was extrapolated to the UK population from Scottish data and an estimated incidence of 0.025% was calculated. 7 The four cases of endophthalmitis in this study represent an incidence of 0.04% for injections given by the NPs, which is favourable relative to the rates observed in the MARINA and ANCHOR studies and similar to that reported by the British Ophthalmological Surveillance Unit. Traumatic lens damage following ranibizumab injection has been reported, 8 but no patients treated by the NP had evidence of inadvertent lens damage on follow-up medical review.…”
Section: Discussionsupporting
confidence: 70%
“…2 The largest UK prospective study identified 47 cases through the British Ophthalmological Surveillance Unit over a 15-month period, but the denominator figure was extrapolated to the UK population from Scottish data and an estimated incidence of 0.025% was calculated. 7 The four cases of endophthalmitis in this study represent an incidence of 0.04% for injections given by the NPs, which is favourable relative to the rates observed in the MARINA and ANCHOR studies and similar to that reported by the British Ophthalmological Surveillance Unit. Traumatic lens damage following ranibizumab injection has been reported, 8 but no patients treated by the NP had evidence of inadvertent lens damage on follow-up medical review.…”
Section: Discussionsupporting
confidence: 70%
“…2 They correctly highlight the need for a proper method of developing and validating questionnaires. In the reference they cite, the authors advocate that a questionnaire should be designed as part of a systematic, prospective case ascertainment system.…”
Section: Sir Reply To Bhavsar Et Almentioning
confidence: 99%
“…Without an attempt to validate the questionnaire, one cannot be certain about the accuracy or validity of the data. 2 Although the authors acknowledge that data regarding povidone-iodine were not collected, the failure to administer povidone-iodine may have been the underlying risk factor for many of the 47 endophthalmitis cases reported. Povidone-iodine is well known to reduce the rate of endophthalmitis after intraocular surgery.…”
mentioning
confidence: 99%
“…These results differ significantly from previous evaluations of medical content on YouTube, which found that o20% of the videos were misleading. 3,4 These studies employed similar methodology but investigated conditions with established medical treatments. Sir, The role of antibiotics in the prevention of post-intravitreal anti-VEGF endophthalmitis: primum non nocere!…”
mentioning
confidence: 99%